2011
DOI: 10.1002/pbc.23037
|View full text |Cite
|
Sign up to set email alerts
|

Late sequelae of symptomatic epidural compression in children with localized neuroblastoma

Abstract: Fifty-eight percent of the children with localized neuroblastoma and symptomatic EC registered in this study developed late sequelae. The severity of motor deficit at diagnosis was the main risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
69
2
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(82 citation statements)
references
References 23 publications
(32 reference statements)
2
69
2
7
Order By: Relevance
“…The association between the primary tumor location and the prevalence of spinal deformity is disputed. Two studies found more spinal deformity with thoracic located tumors, while two other studies did not found such an association …”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The association between the primary tumor location and the prevalence of spinal deformity is disputed. Two studies found more spinal deformity with thoracic located tumors, while two other studies did not found such an association …”
Section: Resultsmentioning
confidence: 92%
“…also found an advantageous outcome for the group treated with chemotherapy in comparison with neurosurgery; however, this difference did not reach statistical significance . The symptomatology at diagnosis (motor deficit and/or sphincter dysfunction) has strong predictive value for sphincter problems experienced at the end of follow‐up …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Follow-up time (52, 99) and concomitant radiotherapy (107, 108) influence the effects of surgery on spinal malalignment. In a study of neuroblastoma survivors, Paulino et al .…”
Section: Resultsmentioning
confidence: 99%
“…(52) observed that those treated with laminectomy developed scoliosis after a median of 23 months, and those treated with radiotherapy developed scoliosis after a median of 68.5 months. Among 98 neuroblastoma survivors with symptomatic epidural compression, the prevalence of spinal deformity among those who had chemotherapy, radiotherapy and surgery was 62.5% compared to those who had chemotherapy and surgery (30%) or surgery alone (50%) (108). …”
Section: Resultsmentioning
confidence: 99%